(untitled) (Nepalese Journal of Management Research, 2024)
The relationship between corporate culture and organizational performance is intricate and influential. Corporate culture encompasses shared values, beliefs and behaviours within a company, shaping its identity. A positive and aligned culture can enhance employee engagement, teamwork, and innovation, ultimately driving organizational success. Effective leadership plays a pivotal role in cultivating a healthy corporate culture, fostering employee satisfaction and commitment. Organisations that prioritize a cohesive and positive culture often experience improved productivity, adaptability, and long-term viability in the competitive business landscape. Understanding and nurturing the interplay between corporate culture and orgainsational performance is crucial for sustained success. However the study discovered that researches on the subject matter remain inconclusive as there are various variables of culture that are yet to be fully explored in research. Therefore, the study recommended that management of organisation should endeavour to establish an acceptable and well appreciated culture by members in order to enhance continuous success and development.